Determinants on share prices behaviour of Bursa Malaysia Stock Exchange - Ismail, Md Khairu Amin; Shaari, Rustam; Abd Khalim, Abi Syakir (Universiti Teknologi MARA, Kelantan, 2018)
The main purpose of this study is to examine the determinants of share price behaviour of Bursa Malaysia Stock Exchange. There are 50 public listed companies were selected randomly from Bursa Malaysia main market. The period of the present study is from 2007 until 2016. Share price is chosen as dependent variable while dividend per share, return on equity, size of firm, and price earnings ratio have been chosen as independent variables in this study. Based on the findings, the results show that dividend per share, return on equity, and size of firm are significant with share price behaviour while price earnings ratio is not significant.